Unclean Hand Detection Machine using Vision Sensor - Faradila, Naim; Rawaida, Jaafar; Nurul Wahidah, Arshad; Rosyati, Hamid; Mohd Najib, Razali (2013)
This paper will discuss about the unclean hand detection using vision sensor for an automated hand wash screening system. Currently the hand wash screening audit is done manually by an expert to monitor the hand under ultraviolet light once it's been washed. Hence, there is a need for more human experts to conduct the screening manually. This project is proposed to automate the hand wash screening audit by using a vision system. The vision system is designed to increase accuracy to detect the unclean area of washed hands. This system will not only detect the unclean area, but will also calculate the percentage of the unclean area which will be used as further analysis of the efficiency of the system. However, we need to build the hand wash prototype using ultraviolet light and a camera that is connected to the computer to process and display the results of hand wash screening.